Enhanced Inflammatory Reaction and Thrombosis in High-Fat Diet-Fed ApoE-/- Mice are Attenuated by Celastrol - Ouyang, Mao; Qin, Tao; Liu, Hengdao; Lu, Junya; Peng, Caixia; Guo, Qin (Experimental and Clinical Endocrinology & Diabetes, 2020)
Objective High-fat diet (HFD) increases the risk of inflammatory reaction and acute arterial thrombosis. Celastrol has been confirmed to regulate inflammatory cytokine levels in atherosclerotic animal models. However, the anti-thrombotic effects of celastrol have remained to be fully demonstrated. The present study was performed to investigate the beneficial effect of celastrol in HFD-induced inflammatory reaction and thrombosis in apolipoprotein (apo)E-/- mice.Materials and Methods Thrombogenic mice model was established using HFD-fed apoE-/- mice. The levels of mRNA and protein were assayed by RT-qPCR and western blotting, respectively. Immunohistochemistry (IHC) staining was performed to measure the protein expression of matrix metalloproteinase-2 and matrix metalloproteinase-9 in the aortic endothelium of HFD-fed apoE-/- mice.Results The results demonstrated that the effect of HFD on inflammatory cytokines in mice with apoE-/- background was reversed by celastrol administration, and celastrol treatment inhibited the NOD-like receptor family, pyrin domain containing 3 (NLRP3)/caspase-1/interleukin-1β signaling cascades in peripheral blood mononuclear cells from HFD-fed apoE-/- mice. In addition, HFD enhanced adenosine diphosphate-induced platelet aggregation in normal C57BL/6 and apoE-/- mice, while celastrol administration reversed this. Furthermore, celastrol inhibited the pro-thrombotic effects of HFD in apoE-/- mice, and the underlying mechanism was mediated, at least partially, through the suppression of matrix metalloproteinase-2 and -9 expression.Conclusions Celastrol administration significantly attenuated HFD-induced inflammatory reaction, platelet aggregation and thrombosis in apoE-/- mice, and celastrol may be used as a drug for the prevention of HFD-induced inflammatory reaction and thrombus.
Keywords: thrombus; inflammation; celastrol; matrix metalloproteinase; NLRP3